Identifikasi Faktor Kimiawi Kulit Durian Sebagai Potensi Sumber Antikolesterol Alami - Maharani, Lila; Zuhro, Fatimatuz (Fakultas MIPA UNM, 2017)
Abstract. The high fat in cooking, the provision by frying, the low consumption of fiber from vegetables, the effects of free radical will gradually cause the buildup of fat and cholesterol in the blood. Albedo durian contains essential oils, flavonoids, and saponins that have the potential in the process of prevention or treatment of diseases associated with free radicals, such as cholesterol. This study aims to determine the potential of local durian albedo and durian montong as a natural agent controlling cholesterol in the body. The study was conducted by analyzing the phytochemical samples of local albedo albedo and durian montong in the laboratory. The results showed that the phytochemical compounds contained in the local durian were equal to the durian montong, which included; saponins, flavonoids, tannins, and triterpenoids. Both samples of albedo durian proved to contain no phytochemical compounds of alkaloids and steroids.Keywords: analysis of phytochemicals, albedo durian, blood cholesterol.l park, herbs vegetation.Â